第56次日本南極地域観測隊気象部門報告2015 - 押木, 徳明; オシキ, ノリアキ; 矢頭, 秀幸; ヤトウ, ヒデユキ; 萩谷, 聡; ハギヤ, サトシ; 西, 秀紘; ニシ, ヒデヒロ; 馬場, 祐介; ババ, ユウスケ; Oshiki, Noriaki; Yato, Hideyuki; et al. (国立極地研究所, 2020)
この報告は第56次日本南極地域観測隊気象部門が，2015年2月1日から2016年1月31日まで昭和基地において行った気象観測結果をまとめたものである．観測方法，測器，統計方法等は第54次隊とほぼ同様である．第55次隊から第57次隊で計画していた地上気象観測装置の更新作業において，第56次隊では風向風速計，温度計，湿度計，積雪計の各測器を設置し，データの取得，確認などを実施した．越冬期間中の特記事項としては，次のものが挙げられる． 1）積雪が深かった．ブリザードの発生回数は平均（24.6回）を上回る29回となり，積雪の深さが増加し，維持することに寄与した．特に，7月17日から19日にかけてのA級ブリザードで積雪の深さは50 cm以上増加し，7月31日及び8月30日には179 cmを記録した．その後，9月25日に185 cmに達した．これらの記録は，それぞれ7月から9月の月最深積雪の第1位となった． 2）昭和基地上空の下部成層圏において，5月から8月，10月から2016年1月の月平均気温はおおむね平年より低く，特に5月の100 hPa面から40 hPa面の指定気圧面で月平均気温の低い方からの記録第1位だった．また，2016年1月には，175 hPa面から125 hPa面の指定気圧面の月平均気温の最低値を記録した． 3）昭和基地上空のオゾン全量は，8月中旬から12月中旬までオゾンホールの目安となる220 m atm-cmを度々下回った．12月も比較的オゾン全量が少ない状態が継続し，12月の月平均オゾン全量は過去2番目に少ない値となった．過去10年と比較してほぼ最低で推移した同月のオゾン全量に対応し，夏至が近い12月1日にはUVインデックスは最大の12.7となり極値を更新した． This report describes the results of meteorological observations at Syowa Station from February 1 st, 2015 to January 31 st, 2016, carried out by the Meteorological Observation Team of the 56 th Japanese Antarctic Research Expedition (JARE-56). The observation methods, instruments, and statistical methods used by JARE-56 were almost the same as those used by the JARE-55 observation team. The operation to replace the surface observation system in Syowa station was carried by JARE-55, JARE-56, and JARE-57. In this operation, JARE-56 installed an anemometer, thermometer, hygrometer, and snow cover meter and operated the new surface observation system as test operation. Remarkable weather phenomena observed during the period of JARE-56 are as follows. 1) The snow depth was considerably large in 2015. The number of blizzards that attacked Syowa station was 29. This number was higher than the average for the period from 1981 to 2010 (24.6) and contributed to increase snow depth and to keep it large. Especially, the snow depth increased 50 cm during the blizzard from July 17 th to 19 th. Thus the snow depth reached 179 cm on July 31 th and August 30 th and 185 cm on September 25 th. These records updated the maximum snow depth of the month in July, August, and September. 2) Monthly ...